2017
DOI: 10.1038/s41598-017-17775-3
|View full text |Cite
|
Sign up to set email alerts
|

Genomic footprints of dryland stress adaptation in Egyptian fat-tail sheep and their divergence from East African and western Asia cohorts

Abstract: African indigenous sheep are classified as fat-tail, thin-tail and fat-rump hair sheep. The fat-tail are well adapted to dryland environments, but little is known on their genome profiles. We analyzed patterns of genomic variation by genotyping, with the Ovine SNP50K microarray, 394 individuals from five populations of fat-tail sheep from a desert environment in Egypt. Comparative inferences with other East African and western Asia fat-tail and European sheep, reveal at least two phylogeographically distinct g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 78 publications
8
41
0
1
Order By: Relevance
“…). Intriguingly, CMPK1 has been identified as being under selection in Egyptian sheep populations adapted to hot dryland (Mwacharo ). The other candidate gene worth noting, identified on BTA24 (0.93–1.19 Mb) and linked to apoptosis, was NFATC1 ( NFAT ).…”
Section: Resultsmentioning
confidence: 99%
“…). Intriguingly, CMPK1 has been identified as being under selection in Egyptian sheep populations adapted to hot dryland (Mwacharo ). The other candidate gene worth noting, identified on BTA24 (0.93–1.19 Mb) and linked to apoptosis, was NFATC1 ( NFAT ).…”
Section: Resultsmentioning
confidence: 99%
“…However, interestingly enough, it also occurred when reports aiming at the identification of genomic signals of adaptation to extreme environments were considered. It is worth pointing out that most studies in this field aimed at the identification of genomic areas related to adaptation to high altitude 10,17 or to high temperature in basically arid environments 15,63 . Such works involved several sheep populations bred in different geographical areas highly contrasting in environments, production systems and goals 14,15,63 .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth pointing out that most studies in this field aimed at the identification of genomic areas related to adaptation to high altitude 10,17 or to high temperature in basically arid environments 15,63 . Such works involved several sheep populations bred in different geographical areas highly contrasting in environments, production systems and goals 14,15,63 . Therefore, the ability to identify selection signatures related to thermotolerance or hypoxia may be affected by the influence of others more likely linked to production or reproduction performance.…”
Section: Discussionmentioning
confidence: 99%
“…According to Xu et al [4] fat tails represent the energy reserve necessary to survive critical conditions such as drought seasons and food shortage. This statement being emphasized by Mwacharo et al [5] who confirmed that the fat-tails are the predominant sheep across the deserts of northern Africa, and in the highlands, semi-arid and arid environments of eastern and southern Africa while the thin-tails occur in Sudan and in the sub-humid and humid regions of West Africa.…”
Section: Introductionmentioning
confidence: 93%